Clinico-Therapeutic Management of Reticular Abscess due to Ruminal Acidosis in Jaffarabadi Buffalo – A Report of Four Cases - N Parmar, Jagruti; L Parmar, Vijay; G Dodia, Piyushkumar; V Mavadiya, Suresh; K Bilwal, Avinash; A Vagh, Arshi (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Reticular abscesses in buffaloes are a frequent complication of traumatic reticuloperitonitis or foreign body syndrome, primarily caused by the anatomical structure and function of the reticulum (Athar et al., 2010). These abscesses often result from foreign body penetration or bacterial infections, causing severe inflammation that can lead to toxaemia and heart failure if left untreated (Abu-Seida and Al-Abbadi, 2016). In addition to trauma, prolonged ruminal acidosis, often due to improper dietary management, is a significant contributing factor (Sharma et al., 2015). When ruminants consume high amounts of rapidly fermentable carbohydrates, such as grains, subacute ruminal acidosis (SARA) can occur, leading to a drop in ruminal pH and weakening of the rumen and reticulum walls, making them more susceptible to bacterial infections and abscess formation (Caldwell et al., 2011). This study documents the clinico-therapeutic management of reticular abscesses due to ruminal acidosis in Jaffarabadi buffaloes.